ANALISIS KEPUASAN WAJIB PAJAK, KUALITAS PELAYANAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KESADARAN WAJIB PAJAK KENDARAAN BERMOTOR PADA KANTOR SAMSAT PUTRI HIJAU MEDAN TAHUN 2021 - Dimas Erlangga Kesuma; Seniwati Sembiring; Tuah Panjaitan (Fakultas Ekonomi Universitas Al-Azhar Medan, 2023)
The purpose of this survey was to test how much awareness people in Medan have about paying motor vehicle tax and to determine whether the application of motor vehicle tax administrative sanctions at Samsat office in Putri Hijau improves taxpayer satisfaction. was to test how effective it was for Enlightenment at Medan Putri Hijau Samsat Office. The survey was conducted at the office of SAMSAT Putri Hijau Medan. The number of samples in this survey was 100 respondents using the sampling method. Data were collected by filling out questionnaires/surveys. The data analysis technique used in this study is multiple linear regression. Based on the analysis results, we find that there is a positive effect on taxpayer satisfaction, no significant impact on the quality of tax services, and tax penalties have a positive effect on taxpayer perceptions. . At the same time, taxpayer satisfaction, quality of tax services, and taxpayer witnesses have a significant impact on taxpayer perceptions.